A chronic granulomatous disease masked by tuberculosis in an young infant - Sahoo, Manas Ranjan; Jondhale, Sunil Nath; Goel, Anil Kumar (International Journal of Contemporary Pediatrics, 2021)
Chronic granulomatous disorder is a rare primary immunodeficiency disorder with phagocytic defect resulting in recurrent bacterial infections. Here we report a 2-year 2-month old male child, who presented with recurrent lymphadenitis and recurrent pneumonia since early infancy. In recent episode he presented with right cervical lymphadenopathy. Biopsy of lymph node revealed confluent necrotizing epithelioid cell granulomas and occasional giant cells but without evidence of tuberculosis and atypical organisms. His dihydrorhodamine 1,2,3 assay (DHR) was positive. Later he responded to prolonged parenteral antibiotics and discharged on itraconazole and trimethoprim-sulhamethaxazole prophylaxis. Here we are going to report a rare case of chronic granulomatous disease whose diagnosis was masked by tuberculosis